HUBUNGAN ANTARA CELEBRITY WORSHIP DENGAN CYBER AGGRESSION PADA PENGGEMAR KPOP USIA DEWASA AWAL DALAM PLATFORM TWITTER - Iffany Nabelliasari; Widyastuti Widyastuti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Cyber Aggression is a behavior where individuals hurt others in cyberspace. This research is intended to examine the relationship between Celebrity Worship and Cyber Aggression in early adult Kpop fans on the Twitter Platform. The research method is quantitative correlation and the data analysis uses Pearson r correlation through JASP with measuring instruments, namely the Celebrity Worship scale with Cyber Aggression. The result of this study indicates that there is a significant relationship between Celebrity worship and Cyber Aggression. Celebrity Worship and Cyber Aggression, obtaining result (r=0,287, p<0,001) this shows that there is a positive relationship between Celebrity Worship and Cyber Aggression. Shows a very significant positive relationship between Cyber Aggression and Celebrity Worship, which means that the higher the value of a person’s Celebrity Worship, the higher of the Cyber Aggression. Then the higher of Cyber Aggression he/she has or vice versa lower of the Celebrity Worship value. The lower of the Celebrity Worship value, is the lower of the Cyber Aggression he/she has.